Multispectral dermatoscopic features of chemical leucoderma with pigmented contact dermatitis - Balakrishnan Nirmal; Borra Santhikiran; Sramana Mukhopadhyay (Wolters Kluwer Medknow Publications, 2018)
Chemical leukoderma is characterized by pigment loss on constant exposure to chemical agents. Its association with pigmented contact dermatitis is rare. Here, we report a 40-year-old female presenting with depigmented macule with surrounding hyperpigmentation over the upper forehead. We used a multispectral dermatoscope by which decreased pigment network was better visualized with blue light, and gray granular dots were better appreciated with yellow light. Shorter wavelengths delineate epidermal features better whereas longer wavelengths highlight dermal features in multispectral dermatoscopy.